The Factor Influencing UTHM Student’s Using YouTube for Academic Achievement - Muhammad Zamirul Hafeez Nor Azwan; Anim Zalina Azizan (Research in Management of Technology and Business, 2024)
YouTube is a popular online video-sharing website. Users can share, watch, and interact with videos that include entertainment and music to educational subjects. The purpose of this study is to measure two main objectives which are to identify the factor usage of YouTube as a learning material for academic achievement and to study the dominant factor that influences the usage of YouTube as a learning material for academic achievement. This study was focused on all UTHM students from Parit Raja with age between 20 to 30 years old. Quantitative methods were used to obtain information by distributing 365 questionnaires to respondents through the medium of google form and sent through applications such as WhatsApp and Telegram. The data obtained was analyzed using the Statistical Package for Social Science (SPSS) version 27 software to obtain strong results. Data analysis shows the factor that influencing UTHM student’s using YouTube are source credibility, information language and accessibility information quality. Limitations include potential survey biases, therefore future study should use a broader technique for more accurate findings.